North Atlantic Micro State Security Governance: Facing Structural, Natural and Political Challenges Historically, Today and in the Future - Bertelsen, Rasmus (Arctic Portal, 2011)
Young researcher Rasmus Bertelsen, United Nations University Institute of Advanced Studies, Japan, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.